INFLUENŢA COMUNICĂRII DIDACTICE ASUPRA CLIMATULUI EDUCAŢIONAL - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2012)
It is obvious that didactic communication by its specific teaching is important for developing an effective and inclusive school climate. Didactic communication directs the work of teachers by boosting their capacity to: a) create a viable lesson plan, b) develop an educational message, c) focus on each student's educational message, taking into account the intellectual, socio-affective and psychomotor peculiarities, d) stimulate continuous improvement of educational action by taking full advantage of the reverse connection to external cycles designed as a prerequisite for self-instruction/selfeducation. It should be mentioned that didactic communication is the main tool in promoting the educational climate which can influence positively or negatively by its peculiarities.